The Salary: Its Protection and Guarantee - Pasco Cosmópolis, Mario (1986)
The salary is an essential element of the employment relationship. Work is, by definition and by substance, paid work, and it is in this dimension that it constitutes the subject matter of labor law, to which the modalities of unpaid human labor, whether slavery or servitude, which the law rejects, whether altruistic or recreational activities, are foreign. The salary represents, therefore, one of the capital issues for legal analysis, not only in its conceptualization, definition, classification and integration, but also in the protection and guarantee of its level or amount, its integrity, its intangibility, its inseverability and unseizability, and its privileges.